Answer: y = 2 or 7
Explanation:Copy and open the bracket
2y² + 5y +63 = (y + 7 )²
expand the right hand expression (y + 7 )², which now becomes
y² + 14y +49 , now equate the 2 together and arrange it into a quadratic structure
2y² + 5y +63 = y² + 14y + 49
2y² - y² + 5y - 14y +63 - 49 = 0
y² -9y + 14 = 0
Now, factorize the expression using grouping or any method
y² -7y - 2y + 14 = 0, considering two factors, when multiplied together gives +14, and when added together gives - 9
Considering the common factors ,it now becomes
y( y - 7) -2(y - 7) =0
(y - 2)(y - 7) = 0
To find the root of y,
when y - 7 = 0
y = 7, and when y- 2 =0, y = 2
Therefore, the solution of the equation is
y = 2, or 7.